Floating alginate beads: Studies on formulation factors for improved drug entrapment efficiency and In Vitro release - Verma A.; Sharma M.; Verma N.; Pandit J.K. (My University, 2025)
Floating calcium alginate beads based on gas-generation technique often suffer from poor drug encapsulation and rapid drug release in the acidic environment of the stomach. To overcome the above mentioned demerits, in the present study we have evaluated the influence of formulation factors such as incorporation of mixtures of gasgenerating agents (NaHCO3 and CaCO3), incorporation of gelatin type B and xanthan gum into the calcium alginate beads prepared by ionotropic gelation in acidic CaCl2 solution. Further, feasibility of floating polyelectrolyte complex (PEC) beads based on sodium alginate (SA) and low molecular weight chitosan (LMWC) to overcome the demerits of floating calcium alginate beads was also investigated. In all experiments ketoprofen was used as model drug. The data from excipient-excipient interaction studies carried out by using FTIR and DSC techniques revealed the PEC formation between SA and LMCH and between SA and gelatin type B, whereas, the data from drug-excipient interaction studies revealed the interaction between ketoprofen and the cations. It was found that all the studied formulation factors markedly affect the entrapment efficiency and drug release in 0.1 M HCl (pH 1.2).